Constantine. Volume 4, The Apocalypse road - Fawkes, Ray (New 52., 2015)
"Trapped on a dying world, John will have to pull off the most daring escape of his life if he's going to survive! Don't miss the debut of new series artist Jeremy Haun (BATWOMAN). Collects CONSTANTINE #18-23"--